Pengaruh Kepemimpinan Kepala Sekolah, Budaya Sekolah dan Motivasi Kerja terhadap Kompetensi Pedagogik Guru - Nurrohman, Moh.; Juliejantiningsih, Yovitha; Maryanto, Maryanto (Jurnal Inovasi Pembelajaran di Sekolah, 2024)
In an effort to improve teacher pedagogical competence, there are several factors that need to be studied, including the principal's leadership, school culture and teacher work motivation. Increasing teachers' pedagogical competence really requires the role of the principal as the holder of the highest level of leadership in the school. Leadership is the ability to influence, move and direct the actions of a person or group of people to achieve certain goals in certain situations. The research approach used is a quantitative approach because research data is in the form of numbers obtained from data conversion in the field in the form of questionnaires and then analyzed using statistics. The type of research used is ex post facto (non-experimental) research. The research results show that the pedagogical competence of State High School teachers in Rembang Regency is very high, as evidenced by the average score percentage reaching 86.75%. The principal's leadership is classified as very high (85.15%), school culture is classified as very high (86.61%) and teacher work motivation reaches 86.57% in the very high category.  There is a positive influence of the principal's leadership on the pedagogical competence of State High School teachers in Rembang Regency. 2. There is a positive influence of school culture on the pedagogical competence of State High School teachers in Rembang Regency. 3. There is a positive influence of work motivation on the pedagogical competence of State High School teachers in Rembang Regency. 4. There is a positive influence of the principal's leadership, school culture and teacher work motivation on the pedagogical competence of State High School teachers in Rembang Regency. Based on the conclusions above, it is known that the independent variables studied both separately and together have a significant influence on the dependent variable. This suggests that improving teacher competency can be done by improving the principal's leadership, school culture and teacher work motivation.